Workshop Penyusunan Program Unggulan OSN di Madrasah Ibtidaiyah Muhammadiyah Tegalampel, Klaten - Muhamad Taufik Hidayat; Nuqthy Faiziyah; Vina Listiawati; Ika Fajar Rini; Surahmat Surahmat (Universitas Mathla'ul Anwar Banten, 2019)
THE WORKSHOP OF COMPILATION OF SCIENCE OLYMPIAD LEADING PROGRAM IN MADRASAH IBTIDAIYAH MUHAMMADIYAH TEGALAMPEL, KLATEN. The purpose of this social service activity were to provide knowledge and insights related to the science olympiad (OSN) to the headmaster and teachers of MIM Tegalampel as well as assisted the compilation of work programs and committee of MIM Tegalampel. Materials that provided were OSN, best practices, and compilation of work program and committee. The model used was a workshop model with lecture, demonstration, question and answer and hands-on practice method. Evaluation was done by disseminating information and motivation to participants and product checklists. Generally, participants claimed that the schedule training was appropriate, time sharing (lectures, group discussions, individual assignments, presentations and games) were also perceived positively by participants. Participants were satisfied with the topics presented and perceived that most of the expectations and objectives of the workshop were fulfilled. The evaluation results indicate that the material delivered can be followed well and there was an increase in knowledge and motivation. In addition, the OSN work program and committee have also been arranged quite well.